An Analysis Of The EST Secondary School Reading Curriculum In Yemen: Approaches And Preparation For Academic Reading At The University Level - Lubna Ali Mohammed Saleh (Universiti Sains Islam Malaysia, 2024)
There are two main purposes of the current present study: 1) To determine the overarching approaches to second language (1.2) reading instruction reflected in the Yemeni EST 3rd grade secondary school reading curriculum and 2) To determine if the curriculum prepares students for the reading skills that they are required to have for reading in English at the tertiary level. The data for the study were collected via curriculum documents reviews as well as from classroom observations in the participating schools. The study examined the types of SLA and 1.2 reading instructional approaches, types of reading tasks and texts, learner and teacher roles, the level of cognitive demands required for the reading tasks as well as the emphasis on reading as the means to achieve the learning outcomes listed in the selected curriculum. The data for this study were analyzed using content analysis. The findings on the SLA theories, second language reading theories, learner roles and teacher roles indicate that there are misalignments between the communicative label of the selected curriculum and its actual theoretical grounding. In contrast to its communicative label, the findings indicate that the Yemeni EST 3rd grade secondary school reading curriculum is highly grounded in the cognitive information processing theory rather than the communicative language teaching theory. In addition, the finding on teachers’ role shows that the teachers primarily act as a director rather than a catalyst while the learner’s role are designed to be primarily as individual tasks rather than pair/group tasks. In terms of preparing students for academic reading in English at the University levels, the types of reading tasks in the selected curriculums does train the students on three types of major reading tasks. Nonetheless EST learners are more frequently trained will reading tasks that required low level of cognitive demands rather than reading task that require higher level of cognitive demands. In terms of type of reading passages, the training on the processing of expository texts is highly inadequate due to a significant inclusion of the narrative texts in the EST curriculum. The findings of the study also demonstrates that that the Yemani EST 3rd grade learners are not trained to process texts in English at a grade level as the majority of reading texts are below the grades level in terms of readability and length. The Yemeni EST 3rd grade reading curriculum explicitly emphasises on the use of reading skill as a means to achieve the listed learning outcomes in the EST curriculum. The findings of the study have implications not only to the Yemeni settings but also to other setting which English is not the first language. The findings of current study are discussed in terms of the alignment of the EST 3rd grade secondary school reading curriculum EST learners for English language in the content areas at the tertiary level.